Spatial and Temporal Variability in Migration of a Soaring Raptor Across Three Continents - Phipps, W. Louis; López-López, Pascual; Buechley, Evan R.; Oppel, Steffen; Álvarez, Ernesto; Arkumarev, Volen; Bekmansurov, Rinur; Berger-Tal, Oded; Bermejo, Ana; Bounas, Anastasios; Alanís, Isidoro Carbonell; de la Puente, Javier; et al. (Frontiers in Ecology and Evolution, 2019)
Disentangling individual- and population-level variation in migratory movements is necessary for understanding migration at the species level. However, very few studies have analyzed these patterns across large portions of species’ distributions. We compiled a large telemetry dataset on the globally endangered Egyptian Vulture Neophron percnopterus (94 individuals, 188 completed migratory journeys), tracked across ~70% of the species’ global range, to analyze spatial and temporal variability of migratory movements within and among individuals and populations. We found high migratory connectivity at large spatial scales (i.e. different subpopulations showed little overlap in wintering areas), but very diffuse migratory connectivity within subpopulations, with wintering ranges up to 4000 km apart for birds breeding in the same region and each subpopulation visiting up to 28 countries (44 in total). Additionally, Egyptian Vultures exhibited a high level of variability at the subpopulation level and flexibility at the individual level in basic migration parameters. Subpopulations differed significantly in travel distance and straightness of migratory movements, while differences in migration speed and duration differed as much between seasons and among individuals within subpopulations as between subpopulations. The total distances of the migrations completed by individuals from the Balkans and Caucasus were up to twice as long and less direct than those in Western Europe, and consequently were longer in duration, despite faster migration speeds. These differences appear to be largely attributable to more numerous and wider geographic barriers (water bodies) along the eastern flyway. We also found that adult spring migrations to Western Europe and the Balkans were longer and slower than fall migrations. We encourage further research to assess the underlying mechanisms for these differences and the extent to which environmental change could affect Egyptian Vulture movement ecology and population trends.